Pentingnya olahraga selama pandemi COVID-19 - Dyah Ayu Woro Setyaningrum (Jurnal Biomedika dan Kesehatan, 2020)
BACKGROUND Many women complain of uncomfortable symptoms a few days before menstruation in the form of emotional problems to discomfort in the abdominal area, this condition is called premenstrual syndrome.Lack of nutrients, one of which is vitamin B6, is a risk factor for premenstrual syndrome. This study was conducted to assess the relationship between vitamin B6 intake and premenstrual syndrome in junior high school students. METHODS The study used an analytical observational method with a cross-sectionaldesign, in 162 students of SMPN 75 Jakarta, which was taken with cluster random samplingand simple random samplingtechniques. Measurement of the incidence of premenstrual syndrome was carried out using sPAF questionnaires and vitamin B6 intake using SQ-FFQ questionnaires. The data from the study were analyzed using thechi-squaretest. The research was conducted after obtaining the approval of the number ethics 7/KER-FK/II/2022. RESULTS The results showed that female students who experienced premenstrual syndrome were mostly aged 15-16 years (20.8%), had menarche at the age of under 12 years (16.4%), did less exercise (15.6%), had a body mass index (BMI) in the category of excess nutrition (25.0%), andconsumed foods that contained enough vitamin B6 (15.0%). The results of the bivariate analysis between free and dependent variables found no meaningful relationship between premenstrual syndrome and age (p = 0.054), menarche age (p = 0.630), exercise (p = 0.726), BMI (p = 0.131), and vitamin B6 intake (p = 1.000). CONCLUSIONS There was no relationship between vitamin B6 intake, sociodemographic characteristics (age, menarche age), exercise, and body mass index (BMI) and premenstrual syndrome.